2^(10x^2-8x-23)+2^(5x^2-4x-12)-3=0
2^(10x^2-8x-24+1)+2^(5x^2-4x-12)-3=0
2*2^(10x^2-8x-24)+2^(5x^2-4x-12)-3=0
2^(5x^2-4x-12) = a > 0
2a^2 + a - 3 = 0
D = 1 - 4*(-3)*2 = 25
a12 = (-1 +- 5)/4 = 1 - 3/2
a1 = -3/2 < 0 нет
a2 = 1
2^(5x^2-4x-12) = 1
2^(5x^2-4x-12)=2^0
5x^2-4x-12 = 0
D = 16 + 4*5*12 = 256 = 16^2
x12 = (4 +- 16)/10 = 2 -6/5
ответ х = {-6/5, 2}
2^(10x^2-8x-23)+2^(5x^2-4x-12)-3=0
2^(10x^2-8x-24+1)+2^(5x^2-4x-12)-3=0
2*2^(10x^2-8x-24)+2^(5x^2-4x-12)-3=0
2^(5x^2-4x-12) = a > 0
2a^2 + a - 3 = 0
D = 1 - 4*(-3)*2 = 25
a12 = (-1 +- 5)/4 = 1 - 3/2
a1 = -3/2 < 0 нет
a2 = 1
2^(5x^2-4x-12) = 1
2^(5x^2-4x-12)=2^0
5x^2-4x-12 = 0
D = 16 + 4*5*12 = 256 = 16^2
x12 = (4 +- 16)/10 = 2 -6/5
ответ х = {-6/5, 2}